Sisterchicks go brit! eaudiobook Sisterchicks series, book 7. - Gunn, Robin Jones (Sisterchicks,, 2017)
CBA best-selling author Robin Jones Gunn sends the Sisterchicks out on another lighthearted and inspiring adventure. This time they travel to England, hoping to fulfill long-held dreams. Although nothing on the trip goes as planned, each detour shows them that God truly knows their hearts. "Robin Jones Gunn makes traversing midlife seem almost welcoming because she has that rare gift of communicating hope amid trial and inner chaos."-FaithfulReader